1991
DOI: 10.2307/2845543
|View full text |Cite
|
Sign up to set email alerts
|

Native American Biological Diversity and the Biogeographic Influence of Ice Age Refugia

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.. Wiley-Blackwell is collaborating with JSTOR to digitize, preserve and extend access to Journal of Biogeography.Abstract. The Wisconsin glaciation divided North America into a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(23 citation statements)
references
References 30 publications
1
22
0
Order By: Relevance
“…This region coincides geographically with an area in which a relatively large, localized genetic discontinuity is also found between Ensatina eschscholtzii oregonensis (Oregon ensatina salamander) and E. e. platensis (Sierra Nevada ensatina salamander; Jackman and Wake, 1994). As suggested for E. eschscholtzii, much local extinction and recolonization has probably occurred in the Lassen region due to at least two main factors: extensive volcanism (Lassen Peak has been volcanically active in the last 100 years; Clynne, 1999;Norris et al, 1997) and the fact that this upland area was subjected to glaciation during the Pleistocene, when ice sheets extended as low as about 1500 m and the regional snow line (the lower limit of perennial snow) was about 2000 m lower than at present (about 4200 m; Kane, 1982;Rogers et al, 1991). Much of the usable habitat for C. bottae would have been eliminated during these periods, which would have prevented contact between rubber boas dispersing from the south and those migrating from the east, north, or west.…”
Section: Discussionmentioning
confidence: 99%
“…This region coincides geographically with an area in which a relatively large, localized genetic discontinuity is also found between Ensatina eschscholtzii oregonensis (Oregon ensatina salamander) and E. e. platensis (Sierra Nevada ensatina salamander; Jackman and Wake, 1994). As suggested for E. eschscholtzii, much local extinction and recolonization has probably occurred in the Lassen region due to at least two main factors: extensive volcanism (Lassen Peak has been volcanically active in the last 100 years; Clynne, 1999;Norris et al, 1997) and the fact that this upland area was subjected to glaciation during the Pleistocene, when ice sheets extended as low as about 1500 m and the regional snow line (the lower limit of perennial snow) was about 2000 m lower than at present (about 4200 m; Kane, 1982;Rogers et al, 1991). Much of the usable habitat for C. bottae would have been eliminated during these periods, which would have prevented contact between rubber boas dispersing from the south and those migrating from the east, north, or west.…”
Section: Discussionmentioning
confidence: 99%
“…Several authors (e.g. Rogers et al ., 1991; Wooding & Ward, 1997; Arbogast, 1999a, b; Arbogast et al ., 2001) have proposed that historical episodes of fragmentation, contraction and subsequent expansion of boreal forest associated with Pleistocene glacial cycles could produce the observed phylogeographic pattern. Both the fossil record (Kurtèn & Anderson, 1980) and levels of mtDNA sequence divergence (Fig.…”
Section: Comparative Phylogeographymentioning
confidence: 99%
“…Although they are close taxonomic relatives, each species communicated risk a slightly different way. Geological evidence suggests the species became isolated 10-100,000 years ago (Hoffmann et al, 1979;Rogers et al, 1991). Nikolsky (1981) found that the alarm calls of arctic ground squirrels (Spermophilus parryi ) isolated for 7,500 years began to diverge enough to be identi ably different.…”
Section: Discussionmentioning
confidence: 99%